Object counter / Azmi Kasim and Sazrol Azizee Ariff - Kasim, Azmi; Ariff, Sazrol Azizee (1999)
Before technology were founded, human calculate the object just using their fingers or by writing. For someone who intelligent, they just reminder in their mind. Now, with a new technology and scientific, many thing become easier. For example we took about our project, where our project have potential to count how many people were go in or go out in the factory through a door. This project by using some component likes ICs, resistor and LEDs. Another else we can use our project such as at the library’s door. It purposes to count how many students use the library. Therefore, our project is purpose to make easy work and comfortable.